Unemployment, Inflation and « Guest Workers »: Comparative Study of Three European Countries - Sturmthal, Adolf (Relations industrielles / Industrial Relations, 1982)
An attempt is made here to show the conditions under which Austria, West Germany and Sweden have come closer than other countries in attaining the double objective of full employment and price stability. Answers appear to lie in the direction of Gross Domes tic Product and the idea of a "Social Contract".